Fracking into the Karoo economy - Young, Adam Alexander (Energy Research Centre, 2017)
With the potential for shale gas extraction in the Karoo region of South Africa, every effort must be undertaken to understand what the effects this transformative industry may have. This paper attempts to explore what effects the industry may have on "small" Karoo towns by creating a demographic and economic baseline for three towns in the region and compares this with a shale gas extraction future. This was grounded in sociological research based on the "Boomtown Model", which attempts to understand the effects extractive industries have on small towns. The thesis finds that small Karoo towns are particularly vulnerable to the negative effects of the Boomtown Model, in light of their current profile which shows the rural economy has been declining for many years, which is coupled with a number of social issues that affect towns such as alcohol abuse and inter-personal violence. This paper concludes that a new shale gas industry will not benefit the residents of the Karoo unless a suitable policy framework is in place that ensures long term beneficiation and mitigates the environmental costs.